Sustaining WEEE collection business in China: The case of online to offline (O2O) development strategies. (1st January 2020) - Zuo, Lyushui; Wang, Chang; Sun, Qiao
Highlights: O2O development strategies are adopted to sustain WEEE collection business in China. Three typical cases of O2O WEEE collection are analyzed using Business Model Canvas. O2O model develops proper systems and channels to support the three flows. Mechanisms of participation, cooperation and profit are built in O2O model. O2O model reduces transaction costs, expands collection scope and scale, and is eco-friendlier. Abstract: WEEE has become a global focus because of its environmental pollution and human health risk and the valuable resources contained. China's ban on solid waste imports reconstructs the global WEEE flow, leading to a more complicated situation for global WEEE recycling that asks for innovative development. The advanced development of the Internet opens new doors to WEEE collection-the first step of recycling, O2O (integrating online platform and offline collection) development strategies are adopted by many companies in China. The exploration of the new model and experiences of WEEE collection in China can provide lessons for other countries. In this study, we decode the business model of three typical cases in China using Business Model Canvas, and discuss and summarize the types, structure characteristics, operating mechanisms and effects of O2O WEEE collection model. The results show that: there are three typical types of O2O WEEE collection model in China, first one derived from internet corporate, second one derived from recycling corporate and third one served as a third-party platform. To ensure the fluency and sustaining of information flow, material flow, and fund flow, O2O WEEE collection model builds information support platforms with user-friendly interfaces, various distribution channels, and accurate pricing systems. To operate the business smoothly, attractive participation mechanism, cooperation mechanism, and multi-level profit mechanism have been constructed. The O2O WEEE collection model enjoys popularity in the capital market and customers for reducing the transaction costs, expanding the collection scope and scale and contributing to efficient and effective WEEE recycling.